Health benefits and limitations of rutin - A natural flavonoid with high nutraceutical value. (December 2021) - Semwal, Ravindra; Joshi, Sunil Kumar; Semwal, Ruchi Badoni; Semwal, Deepak Kumar
Graphical abstract: Highlights: Rutin is a plant-derived natural flavonoid mainly found in buckwheat flour, apples, citrus fruits, tea and red wine. Rutin is found as a major ingredient of several nutraceuticals and placed among the top therapeutically active compounds. Rutin was found effective in the treatment of several diseases like varicosities, haemorrhoids and internal haemorrhage. Rutin has the potential to prevent retinal haemorrhage and cerebral accidents in patients. The presence of four hydroxyl groups and a rutinose molecule in the rutin structure are supposed to be responsible for its biological activities. Abstract: Rutin, a plant-derived natural flavonoid, is considered among the top therapeutically active phytochemicals and one of the major bioactive constituents of a variety of natural foods and brews like buckwheat flour, apples, citrus fruits, tea and red wine. The present work aimed to review the advantages and limitations of rutin based on available literature. Considering its potential role in many health problems, this molecule was critically reviewed for its therapeutical uses and pharmacokinetic properties with the main emphasis on the current advances. Moreover, some solutions to improve the pharmacokinetic profile of rutin are also suggested for its clinical use in the near future. The information on its research outcome was collected online from different authentic scientific databases like Scopus and Google Scholar. Its protective role against heart-related problems, diabetes, inflammation and different microbial infections is evident from earlier research. However, some drawbacks like poor solubility and low bioavailability make its clinical use limited. As a result, various studies on the development of novel drug delivery systems have been conducted in recent years to improve its pharmacokinetic profile and found that the new formulated systems have not only improved pharmacokinetics but also increased the efficacy of rutin. Hence, this molecule can be used clinically after improving its pharmacokinetic properties and revalidating its safety profile in further research.